Evaluation of MALDI Biotyper Mycobacteria Library v3.0 for Identification of Nontuberculous Mycobacteria - Rodríguez-Sánchez, Belén (J Clin Microbiol, 2016)
Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) has demonstrated its ability to promptly identify nontuberculous mycobacteria using the Mycobacteria Library v2.0. However, some species are particularly difficult to identify reliably using this database, providing a low log(score). In this study, the identification power of an updated Mycobacteria Library (v3.0) has been evaluated. Overall, 109 NTM isolates were analyzed with both databases. The v3.0 database allowed a high-level confidence in the identification [log(score) value, ≥1.8] of 91.7% of the isolates versus 83.5% with the v2.0 version (P < 0.01).